Polysaccharides from Russula: a review on extraction, purification, and bioactivities - Cheng, Yan; Gan, Jian; Yan, Bowen; Wang, Peng; Wu, Hao; Huang, Caoxing (Frontiers in Nutrition, 2024)
Russula, a renowned edible fungus, has gained popularity as a functional food among diverse populations due to the abundant presence of amino acids, proteins, and polysaccharides. As the primary constituents of Russula, polysaccharides exhibit a wide range of biological properties, making them an exceptional choice for incorporation into food, medicines, and diverse biotechnological applications. This review provides a summary of the recent research on the extraction, purification, and biological applications of polysaccharides from various Russula spp. Currently, there are many advanced extraction technologies, such as hot water-based extraction, alkali-based extraction, ultrasonic-assisted extraction and microwave-assisted extraction. Hence, the latest progress of extraction technologies, as well as their advantages and limitations will be discusses and summarizes in this review. The separation and purification methods of polysaccharide from Russula were introduced, including ethanol precipitation, deproteinization and gel filtration chromatography. It also focuses on exploring the diverse bioactive capabilities of Russula, including anti-oxidant, anti-tumor, immunomodulatory, anti-inflammation, and anti-bacterial properties. Hence, this review aims to foster a comprehensive understanding of the polysaccharides from various Russula spp. and pave the way for their promising and potential future applications in the medical and functional fields.